Entrepreneurship-Based Curriculum in Merdeka Belajar Era (A Case Study at SMKN Dander Bojonegoro) - Rohmah, Ima Isnaini Taufiqur; Molyono, Molyono (Jurnal Pendidikan Edutama, 2024)
Merdeka Belajar as launched by Ministry of Education, Culture, Research and Technology drive some stakeholders to adapt the learning environment to optimizing the quality of graduate in all level. The aim of this article is to examine entrepreneurship-based curriculum development in vocational high school which is related to the definition of the entrepreneurship curriculum, the basis for its preparation entrepreneurship curriculum, entrepreneurship curriculum development design and entrepreneurial values included in the entrepreneurship curriculum. Entrepreneurship curriculum development is becoming a thing which is important in order to reduce unemployment in the country and increase people's prosperity. Vocational school is a strategic place for developing an entrepreneurship-based curriculum since at this stage, students already have complete thinking abilities so that very potential for them to absorb and apply entrepreneurial values in their learning experiences.